Tartaric acid-derived chiral carbon nanodots for catalytic enantioselective ring-opening reactions of styrene oxide - Zhao, Xinyi; Reva, Yana; Jana, Bikash; Langford, Daniel; Kinzelmann, Marina; Zhang, Zhipeng; Liu, Qi; Drewello, Thomas; Guldi, Dirk Michael; Chen, Xiaoqing (Chemical Communications, 2024)
Chiral carbon nanodots (CNDs) were fabricated through the hydrothermal processing of sulfanilic acid and chiral tartaric acid, exhibiting outstanding catalytic performance for the chiral catalysis of the ring-opening reaction. Furthermore, the catalytic mechanism was proposed to understand the link between the chiral structure and the performance of the catalyst.
CRIS-Team Scopus Importer:2024-09-27